Aluminyum ve aluminyum silisyum alaşımlarının ark fiziksel buhar biriktirme yöntemiyle Mo-N kaplanması - Kılıç, Yasemin (Fen Bilimleri Enstitüsü, 2000)
Hafif malzeme olarak mühendislik uygulamalarında geniş kullanım alanı bulan alüminyum ve alüminyum alaşımlarının önemi hızla artmaktadır. Alüminyum alaşımları bir çok teknolojik alanda, örneğin uçak-uzay ve otomotiv endüstrisinde kullanılan makine parçalarının üretiminde sıkça başvurulan bir malzeme grubudur. Aluminyum-siiisyum (Al-Si) alaşımları ise döküm ile kolaylıkla şekillendirilebiien ve yaygın kullanım alanına sahip alaşım grubudur. Bu alaşımların hafiflikleri nedeni ile motor bloğu olarak kullanım olanakları araştırılmaktadır. Alüminyum ve alaşımlarının zayıf mekanik, korozyon ve tribolojik özelliklere sahip olması ise bazı kısıtlamalar doğurmaktadır. Bu nedenle alüminyum esaslı malzemelerin yüzey işlemleri önem kazanmaktadır. Alüminyum alaşımlarının yüzeylerin değiştirilmesinde klasik akımsız ve elektrokimyasal kaplamalara ilave olarak iyon aşılama, KBB, FBB gibi teknikler de kullanılmaktadır. Alüminyum yüzeylere FBB yöntemleri (ark-FBB ya da magnetron sıçratma) kullanılarak yapılan sert seramik kaplamalar ile aşınma dayanımı yüksek yüzeyler elde etmek mümkündür. Alüminyum ve alaşımlarında en çok görülen aşınma, oksidasyona bağlı sürtünmeden kaynaklanmaktadır. Nitrür bazlı seramik kaplamalarda ise oksijene karşı düşük afinitelerinden dolayı bu tip aşınma görülmemektedir. Piston ve silindir gibi alüminyum motor parçaları için TıN, TîAIN ve CrN gibi seramik kaplamaların uygunluğu aşınma deneyleriyle araştırılmaktadır. Ancak alüminyumun düşük ergime sıcaklığı ve oksijene karşı yüksek afinitesi nedeni ile, yapılan kaplama işlemleri sırasında kaplama ve taban arasında zayıf yapışma gibi bazı sorunlar ortaya çıkmaktadır: Bu çalışmada alüminyum ve aluminyum-siiisyum alaşımlarının yüzeylerine kaplanan Mo-N katmanlarının özellikleri incelenmiştir. Mo-N kaplamalar, diğer nitrür kaplamalara göre daha iyi aşınma-sürtünme özelliklerine ve daha yüksek sertliğe sahiptir. Kullanılan deneysel çalışmalar aşağıda özetlenmiştir Kaplama İşlemleri: Katodik ark-FBB yöntemiyle saf alüminyum ve Al-Si alaşım yüzeylerine Mo-N kaplama uygulanmıştır. Ayrıca Mo-N kaplı başka bir grup numuneye enerjili molibden iyonları ile Mo-N kaplı yüzeyler bombardımana tabi tutulmuştur. Kaplamanın yapısal özelliklerini ve enerjili iyonlar kullanılarak yapılan yayındırma işleminin kaplama yapısına ve özelliklerine etkisini incelemek amacıyla karakterizasyon çalışmaları yapılmıştır. Bu çalışmalar x-ışınları difraksiyonu (XRD) analizleri ile taramalı elektron mikroskobu (SEM) incelemeleridir.

The importance of aluminium and aluminium alloys which are finding widespread use in engineering applications as light alloys is increasing. Aluminium alloys are often selected material group for machine part production in several technological fields such as aerospace-aeronautical industry, automotive industry. Aluminium- silicon (Al-Si) alloys are one of the most widely used alloy group and are easily formed by casting. The possible use of these allloys, due to their low specific weight, in motor block production is being investigated. The poor tribological, corrosion and mechanical properties of these alloys creates limitations. For this reason surface treatment of aluminium based alloys are gaining importance. Besides conventional electroless and electrochemical coatings, additional techniques such as ion implantation, CVD, PVD are used for surface modification of aluminium alloys. By hard ceramic coating of aluminium surfaces with PVD techniques (arc-PVD or magnetron sputtering) it is possible to obtain surfaces with high wear resistance. The most widely observed wear in aluminium and its alloys arouse from the friction due to oxidation. This type of wear is not observed in nitride based ceramic coatings due to their low affinity towards oxygen. The suitability of ceramic coatings such as TiN, TiAIN, and CrN, for motor components like pistons and cylinders are investigated by wear tests. But due to their low melting point and high affinity of oxygen towards aluminium creates some problems during coating processes, such as poor adhesion of the coating to the substrate. In this study the properties of Mo-N coatings that are produced on aluminium and aluminium - silicon alloy surfaces are investigated. Mo-N coatings posses higher hardness and wear and friction properties when compared to other nitride based coatings. The experimental work conducted in this study is summarized below: Coating procedure: Mo-N coatings are applied on pure aluminium and Al-Si alloys by using cathodic arc-PVD technique. Additionally another set of Mo-N coated samples are subjected to energetic molybdenum ion bombardment. Characterization studies are conducted in order to investigate the structural properties of the coating and the effects of energetic molybdenum ion bombardment on the structure and properties of the coating. These studies are x-ray diffraction (XRD) and scanning electron microscopical (SEM) investigations. XIII X-rav analysis: The phase analysis of the samples are conducted by using glancing angle x-ray diffractometer with thin film attachment (Philips Model PW3710 based) using Cu Ka radiation over the 28 range of 20°-120°. Phases in the coating are identified by matching the diffraction peaks with the standard cards from PC-PDF database. Because of the differences observed between the diffraction patterns of coated and energetic ion bombarded surfaces diffraction studies are also conducted by using different angles of incidence and narrow scan ranges. SEM investigations: The substrate material-coating relations and coating properties of the Mo-N coated pure aluminium and Al-Si alloys are investigated from their surfaces and cross sections in SEM and analyzed by energy dispersive spectroscopy (EDS). Additionally the surfaces and cross sections of deformed regions of the coated pure aluminium specimens that are ruptured by using a tensile test machine are investigated by taking into consideration the coating-substrate relation. The findings obtained as a result of this study is summarized below.. It is possible to coat S-MoN on pure aluminium and Al-Si alloys by arc-PVD technique at substrate temperatures of 230-390°C.. In the XRD diffraction patterns taken from the edge and center of the MoN coated pure aluminium structural diferences are observed. In the edge of the samples AlxMoy type compounds were present.. By the application of energetic molybdenum ion bombardment of the MoN coated aluminium and Al-Si alloy surfaces the following results were determined by XRD and SEM investigations:. Aluminium is infiltrated in the coating. The XRD diffaction peaks of the coating shifted towards right, hence the internal stress in the coating decreases. The intensity of the (002) peak of 5-MoN increased and became more distinct. In bombarded Al-Si alloys a two layered structure is formed. In all bombarded aluminium and Al-Si alloys the adhesion of the coating to the subsrate increased substantially These results are the original findings of this study. The energetic molybdenum bombardment of the coating and the resulting structural changes are investigated for the first time in this study.
Mo-N coating of alüminum and alüminium silicon alloys with are physical vapour diposition technique
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2000
Keywords: Alüminyum; Alüminyum alaşımları; Aşınma; Seramik kaplama; Silisyum; Aluminum; Aluminum alloys; Wear; Ceramic coating; Silicon